Proceedings of the 2019 European Conference on Computing in Construction 2019
DOI: 10.35490/ec3.2019.142
|View full text |Cite
|
Sign up to set email alerts
|

Using augmented reality and mixed reality to interpret design choices of high-performance buildings

Abstract: Evaluating building performances, such as the indoor daylight, is usually based on numerical simulation and 2D image illustration. It does not take advantage of emerging Augmented Reality (AR) or Mixed Reality (MR) techniques to intuitively aid the building design. The current study probes into the topic bringing building geometry information together with simulation results into AR/MR environments. After introducing some precedent work in the literature, authors recap the typical workflow and report its appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…The integration of AR and engineering simulation representation was thoroughly introduced in a literature review. 47 50 Ong & Huang reported the integration of finite element analysis (FEA) with a physical model, allowing users to apply virtual loads in AR on real structural frames and directly see superimposed FEA results. 51 Similarly, another group of researchers developed an AR APP and visualized both the beam geometry and FEA results virtually in AR.…”
Section: Visualizing Design Geometries With Simulation Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The integration of AR and engineering simulation representation was thoroughly introduced in a literature review. 47 50 Ong & Huang reported the integration of finite element analysis (FEA) with a physical model, allowing users to apply virtual loads in AR on real structural frames and directly see superimposed FEA results. 51 Similarly, another group of researchers developed an AR APP and visualized both the beam geometry and FEA results virtually in AR.…”
Section: Visualizing Design Geometries With Simulation Resultsmentioning
confidence: 99%
“…59 Structural components and their behaviors are also co-visualized in MR. 60 Not restricted to static simulations, some studies used real illuminance sensors to measure indoor illuminance data and visualized it in MR. 46 By using a server-based system, one study allows multiple MR devices to simultaneously display 3D architectural models with daylighting simulations. 61 However, some researchers noted that showing virtual building design solutions in not-related physical surroundings has limited meaning because they do not have any practical correlation or interaction, wasting the main advancement of MR. 50…”
Section: Visualizing Design Geometries With Simulation Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers have investigated the applicability of different 3D data formats to integrate the CFD simulation dataset with AR/VR. STL [26] [27], 3DS [28], VRML [29][30][31][32], FBX [31][32][33], DAE [34], and X3D [26] were commonly applied with several CFD solvers, post-processors, and 3D computer graphics software to achieve the integration. It is observed that complex structure of CFD dataset and arbitrary nature of data processing make a comparison among studies almost impractical.…”
Section: Data Processing: Software and Data Handling Challengesmentioning
confidence: 99%